Analysis of English languange learning in grade 5 SDN 106161 Medan Estate, Percut Sei Tuan Sub-district, Deli Serdang Regency - Fitra, Aidil; Shabilla, Naura Ayu (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to describe (1) What are forms of literacy skills in eanglish language learning?, (2) What is the level of dificulty of knowledge of fiveth grade students in literacy during English learning at SDN 106161 Medan Estate, Percut Sei Tuan Sub-district, Deli Serdang Regency. The subject of this study consisted of the principal, English teachers and fiveth grade students. The type of this research is descriptive qualitative. The data collected were documents from the English teacher. English teacher as well as the participal. Data sources are divided into two, namely primary data sources in the form of the results of data collection using observation, interviews questionnaries whilw secondary data sources school profile, lesson schedule, student list, and list of educators. Data validity is caried out by means of data triangulation in the proccess consists of three interelated stages, bamely data reduction, data persentation and conclusion making. The results of the study revealed that the forms namely listening, speaking, writing, and reading. The lecel dificulty in writing seen form the analysis of interview data, questonnaires in and observation.